2021
DOI: 10.1021/acsabm.0c01536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Degree of Acetylation of Chitin Nonwoven Fabrics for Promoting Wound Healing

Abstract: Chitin and chitosan have been extensively used as wound dressings because of their special functions to promote wound healing. However, there was little focus on the effects of the degree of acetylation (DA) on wound healing. In this work, the regenerated chitin nonwoven fabrics with DA values of 90, 71, 60, and 42% were prepared, and the morphology and physical performances of the fabrics were characterized. Moreover, the effects of DA of the chitin nonwoven fabrics on wound recovery were studied with a full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…3e). Noticeably, chitin has been widely employed as dressings to promote wound healing, 47,48 so CG hydrogels could promote the wound closure to a certain extent, and the mupirocin group demonstrated a speeding tendency to wound healing compared to the CG hydrogel-treated group, which may be attributed to the controllable infection. Quantitative wound closure rate analysis is shown in Fig.…”
Section: Assessment Of In Vivo Antibacterial Ability and Woundhealing...mentioning
confidence: 99%
“…3e). Noticeably, chitin has been widely employed as dressings to promote wound healing, 47,48 so CG hydrogels could promote the wound closure to a certain extent, and the mupirocin group demonstrated a speeding tendency to wound healing compared to the CG hydrogel-treated group, which may be attributed to the controllable infection. Quantitative wound closure rate analysis is shown in Fig.…”
Section: Assessment Of In Vivo Antibacterial Ability and Woundhealing...mentioning
confidence: 99%
“…Nano-chitin could be obtained by the "top-down" method (e.g., acid hydrolysis, 58 mechanical treatment, 59 TEMPO-mediated oxidation, 60 and tandem molecular intercalation, etc.) 61 and the "bottom-up" method (e.g., wet-spinning method, 62 self-assembly method, 63 and dissolution-regeneration method, etc.). 64 Shi et al 65 reported a "building block reorganization" strategy to prepare chitin-based DN film.…”
Section: Chitin-based Dn Hydrogelsmentioning
confidence: 99%
“…5–7 Owing to these desirable characteristics, chitin has recently attracted substantial research attention and has been widely used in numerous application areas, including food, medicine, agriculture, and other related fields. 8–10 In particular, chitin has been processed into a number of organo-nitrogen containing chemicals. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Owing to these desirable characteristics, chitin has recently attracted substantial research attention and has been widely used in numerous application areas, including food, medicine, agriculture, and other related elds. [8][9][10] In particular, chitin has been processed into a number of organonitrogen containing chemicals. 11,12 Every year, approximately 6-8 million tons of crustacean shell waste are discarded by the seafood industry, thus simultaneously wasting resources and polluting the environment.…”
Section: Introductionmentioning
confidence: 99%